APPLICATION OF GEOGRAPHIC INFORMATION SYSTEMS IN THE CONTEXT OF REFORMING THE HEALTHCARE OF UKRAINE AND MEDICAL SUPPORT OF THE ARMED FORCES OF UKRAINE - Fedchenko, O.; Lytvynenko, N.; Pinchuk, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The possibilities of geographic information systems (GIS) application in the context of reforming the health care system of Ukraine and medical support of the Armed Forces of Ukraine have been studied. GIS helps to provide timely medical care in emergencies – natural disasters, adverse weather conditions, military conflicts, riots, when decisions must be rapid. GIS-analysis increases the efficiency of both routine tasks and planning at all levels of the government. The experience of using GIS at different stages of health care reform and development in the world's leading countries shows that the widespread use of geospatial technologies can significantly improve the management of data, material and human resources, understanding of factors and impacts on health care. The modern challenges require the health care system of our country and medical support of the Armed Forces of Ukraine to use advanced information technologies for the collection, management, analysis, visualization and dissemination of data that can largely provide the geographical information systems. Without GIS, it would be difficult to imagine effective work in crises, emergencies or in the context of military conflict, the successful operation of that depends on people's lives and health. The article studies the possibilities of using geographic information systems (GIS) in the context of health care reform in Ukraine. The experience of using GIS at different stages of health care reform and development in the world's leading countries shows that the widespread use of geospatial technologies can significantly improve the management of data, material and human resources, understanding of factors and impacts on health care. GIS analysis increases the efficiency of both routine tasks and planning at all levels of management. It would be difficult to imagine effective work in crises, emergencies or during military conflicts of many organizations, on the successful performance of which people's lives and health depend, without using GIS. Today's challenges require our country's healthcare system to use advanced information technology to collect, manage, analyze, visualize, and share data that geographic information systems can provide to a large extent. The article considers examples of problems and tasks that can be solved by certain GIS tools. The challenge staysin working with data that is often provided on paper or in formats that are hard to process and store. This organizational and financial problem will continue until health facilities are equipped with necessary hardware, software and staff training. Regarding data that has a spatial component, this issue can be solved with the help of server GIS and geoportal technology, which are able to organize the work with data, sharing for large number of people, data collection, and availability of geospatial services for use in any time and place. Equally promising in the field of health care is the use of GIS-analysis tools that allow to obtain the data needed to make informed decisions, forecast and plan further activities in the short and long term. Ukraine is on the way to strengthening the informatization of the health care system. GIS should play an important role in this process as the main tool for working with spatial information.
Keywords: geographic information system, health care, medical support, spatial analysis, information technologies, geoportal